Pembuatan Biofertilizer sebagai Penunjang Pendapatan di SLB-C Karya Bakti, Purworejo - Wulandari, Dyah; Alberta Rika Pratiwi; Theresya Amelia Prabowo; Cindy Fiolita Graciela (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
The growing global population demands increased food productivity, which can be achieved using fertilizers. However, inorganic fertilizers harm the environment and leave chemical residues, making organic and biofertilizers a sustainable alternative. This initiative aims to enhance skills and inclusive learning for students with special needs while increasing economic and educational value, particularly in biofertilizer production at SLB-C Karya Bhakti, Purworejo. Biofertilizers contain beneficial microorganisms that support soil fertility and plant growth by breaking down nutrients, boosting disease resistance, and enhancing plant development. Unlike chemical fertilizers, biofertilizers are environmentally friendly and leave no harmful residues. They are produced using growth media like husks and fermented through solid-state or submerged fermentation methods. Proper packaging, such as vacuum sealing or PET-nylon-PP materials, is essential to maintain microbial viability and quality. At SLB-C Karya Bhakti, biofertilizers support plant growth in the school garden, actively involving students with special needs. Their use enhances food literacy, influences dietary choices, and improves economic conditions within the school. Additionally, this initiative fosters health and social development among students with disabilities, empowering them with valuable agricultural skills for a more inclusive and sustainable future.